Analisis Tindak Tutur Direktif dalam Manga Dandadan Volume 1 : Chapter 1 - Mochammad Alwan Al Ataya; Rangga Wasita Ningrat; Jonathan Cristiano Rabika; Syah Bintang; Humannisa Rubina Lestari (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
This study investigates directive speech acts in Chapter 1 of the Japanese manga *Dandadan*, focusing on how characters use language to influence others’ behavior. The objective is to classify the types of directive utterances and analyze their pragmatic functions based on the speaker and context. A qualitative descriptive method was employed, using pragmatic theory to analyze speech data taken directly from dialogue panels. The analysis identified nine instances of directive speech acts, which include commands, prohibitions, invitations, and requests. Ayase Momo emerges as the character who produces the most directive utterances, predominantly in the form of commands and prohibitions, indicating her dominant and assertive communication style. Okarun, in contrast, tends to use polite requests and prohibitions, suggesting a more cautious and respectful approach. The findings reveal that the types of directive speech acts used are closely related to each character’s personality and the emotional context of the scene. These results underscore the role of speech acts in character development and narrative dynamics within manga. The study’s implication lies in showing how linguistic choices in manga dialogue reflect interpersonal power relations and emotional intensity. Future research is encouraged to explore directive speech acts across multiple chapters for broader insights.